Dating the early phases under the temenos of the Qaṣr al-Bint at Petra - Renel, F.; Mouton, M.; Augé, C.; Gauthier, C.; Hatté, C.; Saliège, J-F.; Zazzo, A. (Proceedings of the Seminar for Arabian Studies, 2012)
The excavations carried out by the French Archaeological Expedition at the Qaṣr al-Bint (Petra) revealed a dwelling area that predates the cultic complex. The earliest Phase I is attested by small terrace walls, few installations, and sparse material. The surface explored by a few soundings is narrow, however. The material associated with these levels, the pottery and the numismatic finds, as well as the ¹⁴C dates, point to an occupation starting at the beginning of the fourth century BC. The levels of the later architectural Phase II are characterized by well-lined finely plastered stone walls and regular floors covered with slabs. These architectural remains show an established, permanent settlement on the left bank of the Wādī Mūsā dating back to the third century BC.